(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2016)
Vertical maxillary excess is associated with gummy smile, incompetent lip, bimaxillary proclination, Angle’s class-I or class-II malocclusion with or without retogenia. After proper evaluation preoperative orthodontic treatment was performed in every cases and superior repositioning of the maxilla by Le Fort-I osteotomy is presented. Three patients with maxillary excess associated with retrogenia or microgenia were treated with this technique in combination with genioplasty. The maxillary segment was repositioned a maximum of 7.0 mm superiorly at point A. The mandible autorotated anterosuperiorly to achieve sound occlusion. Point B moved 1.0–3.0 mm anteriorly and 5.0–8.0 mm superiorly. The pogonion moved 4.0 mm anteriorly in a case done without genioplasty and the pogonion moved maximum 8.0mm in case done in combination with genioplasty. All patients obtained sound occlusion and a good profile after the operation. Almost no skeletal relapse was observed during 3 years of postoperative follow-up. Amount of gingiva showing during smile was ranges from 5.0mm –7.0mm which was 0-2.0mm after superior repositioning of the maxilla. Ban J Orthod & Dentofac Orthop, April 2016; Vol-6 (1-2), P.1-5